2011
DOI: 10.4314/ijest.v3i4.68546
|View full text |Cite
|
Sign up to set email alerts
|

Machinability of glass fiber reinforced plastic (GFRP) composite materials

Abstract: This paper deals with the study of machinability of GFRP composite tubes of different fiber orientation angle vary from 30 0 to 90 0. Machining studies were carried out on an all geared lathe using three different cutting tools: namely Carbide (K-20), Cubic Boron Nitride (CBN) and Poly-Crystalline Diamond (PCD). Experiments were conducted based on the established Taguchi's Design of Experiments (DOE) L 25 orthogonal array on an all geared lathe. The cutting parameters considered were cutting speed, feed, depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…They evaluated the cutting parameters based on delaminate factors, surface roughness, international dimensional precision, and cutting parameters in two different GFRP composite materials. They showed that feed rate was the most prominent parameter affecting cutting force and that surface roughness increased with feed rate and decreased with cutting speed, which was also confirmed by other authors [6,7,10,16] . Kalla et al [8] developed a methodology for estimating cutting forces in carbon-fiber-reinforced polymers by using helical end mill in various fiber orientations.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…They evaluated the cutting parameters based on delaminate factors, surface roughness, international dimensional precision, and cutting parameters in two different GFRP composite materials. They showed that feed rate was the most prominent parameter affecting cutting force and that surface roughness increased with feed rate and decreased with cutting speed, which was also confirmed by other authors [6,7,10,16] . Kalla et al [8] developed a methodology for estimating cutting forces in carbon-fiber-reinforced polymers by using helical end mill in various fiber orientations.…”
Section: Introductionsupporting
confidence: 85%
“…In this concept, contradictory results are available in the literature. While some colleagues are claiming that cutting speed significantly affects surface quality [13, 14, 16 -19, 21, 22] , some others are claiming that it does not affect significantly [6,7,15,20,22] . The inconsistency arises perhaps from the experimental environment and the tools used.…”
Section: Influence Of Feed Rate and Cutting Speed On Surface Roughnessmentioning
confidence: 99%
See 2 more Smart Citations
“…After then predicated thrust force values and measured thrust force values through experiments had been compared with each other. Hussain et al (2011) developed a surface roughness and cutting force prediction model for machining GFRP tubes using RSM by using carbide tool (K 20 ), cubic boron nitride (CBN) and polycrystalline diamond tool. Four parameters namely cutting speed, feed, depth of cut and work piece (fibre orientation) were selected to minimise the surface roughness and cutting forces.…”
Section: Introductionmentioning
confidence: 99%